2016
DOI: 10.1017/s0007114516002956
|View full text |Cite
|
Sign up to set email alerts
|

Dietary choline and betaine intake, choline-metabolising genetic polymorphisms and breast cancer risk: a case–control study in China

Abstract: Choline and betaine are essential nutrients involved in one-carbon metabolism and have been hypothesised to affect breast cancer risk. Functional polymorphisms in genes encoding choline-related one-carbon metabolism enzymes, including phosphatidylethanolamine N-methyltransferase (PEMT), choline dehydrogenase (CHDH) and betaine-homocysteine methyltransferase (BHMT), have important roles in choline metabolism and may thus interact with dietary choline and betaine intake to modify breast cancer risk. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
4
8
1
Order By: Relevance
“…The present study showed a robustly favorable relationship between serum choline and PLC. This was consistent with several previous studies [ 39 43 ] and with our previous case-control study, which reported an inverse association between dietary choline intake and PLC risk [ 11 ]. To date, only one case-control study, including 297 male HCC patients and 631 male matched controls, has reported on the relationship between serum choline and HCC risk [ 13 ], in which the favorable role of choline was also found.…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed a robustly favorable relationship between serum choline and PLC. This was consistent with several previous studies [ 39 43 ] and with our previous case-control study, which reported an inverse association between dietary choline intake and PLC risk [ 11 ]. To date, only one case-control study, including 297 male HCC patients and 631 male matched controls, has reported on the relationship between serum choline and HCC risk [ 13 ], in which the favorable role of choline was also found.…”
Section: Discussionsupporting
confidence: 94%
“…With the lower level in LNM-positive patients, betaine may be a potential diagnostic biomarker distinguishing LNM-positive GC patients from LNM-negative ones. Our findings together with the previous studies (Sun et al 2016 ; Du et al 2016 ) proved that betaine might play a critical role in the process of LNM of GC. Therefore, dietary choline and betaine intake with a fixed dose may alleviate GC.…”
Section: Discussionsupporting
confidence: 89%
“…The richest sources of total choline are foods of animal origin [ 2 ], which may not be consumed on a daily basis. The relationship between low choline, or betaine, intakes and an increased risk of adverse health outcomes has been described in several studies [ 49 , 50 , 51 , 75 , 176 , 177 ]. However, other studies have found no or only a weak association between choline or betaine intakes and these adverse health outcomes [ 73 , 96 , 178 ].…”
Section: Dietary Assessment Methods and Validationmentioning
confidence: 99%